ECOLOGICAL WATER SYSTEM ASSESSMENT ACCORDING TO PHYTOPLANKTON SPECIES WEALTH - Sukhodolska, Iryna; Нlinska Svitlana; Lohvynenko, Iryna (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
This study presents the data about species composition, phytoplankton population and biomass of the Ikva. Bioindication analysis has been explored considering water plants indicative characteristics. It has been revealed that according to species composition such section representatives as Chlorophyta, Bacillariophyta and Euglenophyta have been provided in a preference. The river phytoplankton population and biomass have been changing from 389,6 to 7070,8 thousand C/L and biomass has been raising from 0,15 to 4,07 mg/L. The author highlights that in water column according to bioindicative characteristics benthos and plankton benthos water plants forms, geographic location cosmopolites, indifferent ones towards pH and degree of salinity balance, indicators of average water flow, temperate temperature conditions, faintly acid and weakly alkaline waters dominate. The study points out the important place of meso saprobionts. According to Pantle-Buk’s (in Sladechek’s modification) level of organic pollution river water belongs to the third grade of quality. In the response to Vatanabe’s system river water has been characterized by temperate organics (evrosaprobs). Ecological and geographical characteristic of river plankton plants gives a possibility to forecast water coen conditions to simulate anthropogenic factors influence on water reservoirs conditions.